The Influence of E-WOM on Visit Decisions to the Jasmine Park Tourism Destination in Cisauk, Tangerang Regency, Banten Province, Indonesia - Habibie, Fachrul Husain; Aryapranata, Ariawan; Rasyid, Yuliansyah Al; Hermanto, Sigit; Adsena, Yogi Priya (Jurnal Ilmiah Hospitality Management, 2025)
This study aims to analyze the influence of Word of Mouth (WOM) and Electronic Word of Mouth (E-WOM) on the decision to visit the Jasmine Park Cisauk tourist destination. The background of this research is driven by the growth of new tourist destinations increasingly relying on informal communication channels to influence visitor decisions. The research uses a quantitative method with a survey approach, where data was collected through questionnaires from 105 respondents. The results show that both WOM and E-WOM have a significant effect on the visit decision, with E-WOM having a stronger influence. This finding highlights the importance of social media and digital reviews in the decision-making process for visiting new tourist destinations, especially for digitally active young tourists.